Efficiency of coconut water immersion inhibiting browning incidence on cut-surface of fresh-cut Gala apples during storage - Suriyan Supapvanich; Dararat Anartnet; Chutima Krungpree (My University, 2018)
The purpose of the work was to investigate the efficiency of coconut water preventing browning incidence of fresh-cut product using ‘Gala’ apple as the fruit model. The fresh-cut apples were dipped in coconut water at the concentration of 0, 50 and 100% for 2 min and then kept at 4 ± 1 °C for 7 days. Browning-related parameters such as browning index (BI), browning score (BS), lightness (L * ), whiteness index (WI), total colour difference (ΔE * ), total phenols (TP), and polyphenol oxidase (PPO) activity were determined. The result showed that visual appearance of the fresh-cut apple was maintained by coconut water dip. Coconut water dip apparently lowered BI, BS and ΔE * increases and maintained L * and WI throughout the storage. The increases in TP and PPO activity of the fresh-cut apples were inhibited by coconut water dips. No significant difference in browning prevention efficiency of the both 50 and 100% coconut water dips was found. Thus 50% coconut water dip is an effectively natural alternative preventing browning incidence of fresh-cut products.
Keywords: Browning; Postharvest Quality and Shelf Life Management